8 Must have qualities of Effective Leader - R N Misra (Mumbai Industrial Relation of India, 2023)
A leader with a clear vision, sets the right example, and demonstrates integrity is a leader who is respected for their integrity. Effective communication involves sharing valuable information, asking intelligent questions, and clarifying misunderstandings. Making hard decisions with limited information is crucial for effective leadership. Recognizing success is a powerful habit for inspiring leaders. Empowering others requires a sense of ownership and meaning in their work. Finally, motivating and inspiring their team is essential for success. By investing time in their strengths, needs, and priorities, leaders can drive their teams forward with passion and enthusiasm.
Keywords: Leader; Integrity; Hard Decisions; Motivate and Inspire